Cochrane Database of Systematic Reviews 2014
DOI: 10.1002/14651858.cd011034
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and educational interventions for subfertile men and women

Abstract: Analysis 2.9. Comparison 2 Educational interventions versus usual care or attentional control, Outcome 9 Discontinuation of fertility treatment..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In a systematic review of 20 randomized controlled trials that examined the effects of psychosocial interventions on the pregnancy rates, mental health, and marital function of infertile couples, it was found that depression and stress were not relieved (Ying, Wu, & Loke, 2016). A Cochrane review of 39 studies revealed that psychological and educational interventions had effects on mental health, including distress, but live births or current pregnancy rates were uncertain because of the very low quality of evidence of the studies (Verkuijlen, Verhaak, Nelen, Wilkinson, & Farquhar, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review of 20 randomized controlled trials that examined the effects of psychosocial interventions on the pregnancy rates, mental health, and marital function of infertile couples, it was found that depression and stress were not relieved (Ying, Wu, & Loke, 2016). A Cochrane review of 39 studies revealed that psychological and educational interventions had effects on mental health, including distress, but live births or current pregnancy rates were uncertain because of the very low quality of evidence of the studies (Verkuijlen, Verhaak, Nelen, Wilkinson, & Farquhar, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…15,[31][32][33][34][35] The NGT created awareness among participants that women with infertility require health education about treatment options, as well as prevention and causes of infertility. Studies 14,[35][36][37] have shown that educational measures should focus on increasing women's knowledge and skills so that they experience a reduced psychological burden during infertility treatment. Information offered about causes and the medical and psychological impacts of different infertility treatment options increases health care users' feelings of satisfaction with medical and emotional care.…”
Section: Discussionmentioning
confidence: 99%
“…Information offered about causes and the medical and psychological impacts of different infertility treatment options increases health care users' feelings of satisfaction with medical and emotional care. 14,[35][36][37] Providing preliminary information about infertility is one of the most effective ways to start implementing psychosocial care, and it is simple, efficacious, and feasible compared with other interventions. 38 Health education may also help reduce gender discrimination against women with infertility in low-and middle-income countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infertility is a common problem, which, according to the available data, affects around 48.5 million people worldwide (Verkuijlen et al 2016). It is defined as the absence of conception after 12 months of regular unprotected sexual intercourse (Zegers-Hochschild et al 2009).…”
Section: Introductionmentioning
confidence: 99%